Investigation Of Single Stage Ë/4 Transformer Matching Network To The X-Circular Polarized Antenna - Abd. Aziz, Mohamad Zoinol Abidin; Ahmad Mufit, Nur Alyaa Diyana; Suaidi, Mohamad Kadim; Rahim, M.K.A (Penerbit Universiti, UTeM, 2012)

(untitled)
This technical paper present 2 design of x-circular polarized with slanted rectangular slot microstrip patch antenna.4 different circular polarized wave is feed by using single port in X-form is at 450,1350,2250 and 3150. The combination of 4 patches for design 1 is without using quarter wave impedance matching technique and design 2 refer to the design x-circular polarized with slanted rectangular slot microstrip patch antenna with single stage transformer.The designs are simulated using Computer Simulation Technology (CST) with dielectric constant,εr=4.3,loss tangent,tan δ=0.019 and thickness of substrate,t=1.6mm.The simulation results for ther return loss,bandwidth,gain,directivity and polarization have been compared.The λ/4 transformer matching network can improve the antenna performance especially the gain and efficiency.